Geographic information system (GIS)-based image analysis for assessing growth of Physarum polycephalum on a solid medium. Issue 1 (December 2015) - Tran, Hanh; Stephenson, Steven; Tullis, Jason
Abstract Background The conventional method used to assess growth of the plasmodium of the slime moldPhysarum polycephalum in solid culture is to measure the extent of plasmodial expansion from the point of inoculation by using a ruler. However, plasmodial growth is usually rather irregular, so the values obtained are not especially accurate. Similar challenges exist in quantification of the growth of a fungal mycelium. Results In this paper, we describe a method that uses geographic information system software to obtain highly accurate estimates of plasmodial growth over time. This approach calculates plasmodial area from images obtained at particular intervals following inoculation. In addition, the correlation between plasmodial area and its dry cell weight value was determined. The correlation could be used for biomass estimation without the need of having to terminate the cultures in question. Conclusion The method described herein is simple but effective and could also be used for growth measurements of other microorganisms such as fungi on solid media.